Quantification of Similar Neurodegeneration Across Geriatric Concussions and Alzheimer's Disease. (17th December 2021) - Irimia, Andrei; Rostowsky, Kenneth
Abstract: Geriatric mild traumatic brain injury (mTBI) is a risk factor for Alzheimer's disease (AD), but few studies have studied how the neuroanatomic effects of these conditions can converge onto similar brain structure trajectories. Here we use magnetic resonance imaging to investigate similarities between mTBI and AD across both white and gray matter (WM and GM, respectively) using measures like fractional anisotropy (FA, a surrogate measure of WM integrity) and cortical thickness. We identify statistically significant similarities in neurodegeneration across mTBI (N = 33; age µ = 63 years (y), σ = 11 y) and AD (N = 66; age µ = 76 y, σ = 9 y) by testing for statistical equivalences of mean FA and cortical thickness. Both WM and GM are found to exhibit significant similarities in how mean FA and cortical thickness decrease, respectively, across mTBI and AD. For WM, the broadest spatial extent of statistical similarity between conditions, quantified as percentages of structures' volumes, is found within the superior fronto-occipital fasciculus (left (L): 91%, p < 0.05; right (R): 95%, p < 0.05), and in the crura of the fornix (L: 65%, p < 0.05; R: 80%, p < 0.05). Across mTBI and AD, cortical thinning trajectories are most similar in the superior precentral sulcus (L: 91%, p < 0.05; R: 100%, p < 0.05), and anterior lateral sulcus (L: 75%, p < 0.05; R: 86%, p < 0.05). Future studies should leverage such findings to identify AD risk factors in mTBI patients.